The effects of religiosity and ethnicity on money attitudes among Malaysians / Mohammadreza Moalemi - Moalemi, Mohammadreza (2013)
This study focuses on the relationship between different demographic characteristics and Money Attitudes among Malaysians. Also it looks at the effect of religiosity on money attitudes of individuals. A total number of 337 responses were taken into account to analyze the related hypotheses. This study used the measurement proposed by Klontz, Britt, Mentzer, & Klontz (2011) to measure the money attitudes of Malaysians. This measurement identifies four distinct money beliefs namely, money avoidance, money worship, money status, and money vigilance. According to the results of the statistical analyses, less educated, lower net-assets individuals, and those who has been in lower middle-class group during childhood are more money avoidant people than others. Less religious individuals have more money status and more money worship attitudes than religious people. Males and singles show more money worship attitudes than females and married individuals. Younger individuals, Malays, and Muslims show more money vigilant attitudes than others groups. Also lower income individuals show more overall money attitude score comparing to higher income persons. Overall the results of this study can help financial practitioners in Malaysia to have a better understanding of different demographic groups’ attitudes toward money and provide them with better financial planning and instruction.